PERAWATAN FASILITAS KAMAR OLEH ROOM BOY DI HOTEL GRAND ELITE PEKANBARU - Cindy Shenora; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Grand Elite Hotel Pekanbaru is the first luxury international business hotel in the Malay heritage city of Pekanbaru (Riau), Sumatra island from Core Hospitality International which offers customers a unique and extraordinary experience with a very comfortable, affordable and irresistible choice, while